2016
DOI: 10.1038/labinvest.2015.123
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA-HOTAIR affects chemoresistance by regulating HOXA1 methylation in small cell lung cancer cells

Abstract: Homeobox (HOX) transcript antisense RNA (HOTAIR), a long intergenic noncoding RNA (lincRNA), has been reported to play an oncogenic role in various cancers including small cell lung cancer (SCLC). However, it is not known whether HOTAIR can modulate chemoresistance in SCLC. The aim of this study is to investigate the roles of HOTAIR in chemoresistance of SCLC and its possible molecular mechanism. Knockdown of HOTAIR was carried out in SCLC multidrug-resistant cell lines (H69AR and H446AR) and the parental cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 27 publications
2
73
0
Order By: Relevance
“…Furthermore, the methylation, and transcription of PCDH10 were restored by pcDNA-HOTAIR in GIST cells previously treated with siRHOTAIRs. Our findings were supported by recent papers caliming that HOTAIR can modulate the methylation of target genes [1720]. …”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the methylation, and transcription of PCDH10 were restored by pcDNA-HOTAIR in GIST cells previously treated with siRHOTAIRs. Our findings were supported by recent papers caliming that HOTAIR can modulate the methylation of target genes [1720]. …”
Section: Discussionsupporting
confidence: 88%
“…In addition, studies showed that the long non-coding RNA HOTTIP promotes gemcitabine resistance by regulating HOXA13 in pancreatic cancer [14]. Our laboratory also reported that lncRNA HOTAIR affects chemoresistance by regulating HOXA1 methylation in SCLC [18]. However, functional roles of lncRNAs in SCLC have not been well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Fang et al testified HOTAIR recruited HOXA1 by RNA immunoprecipitation. HOTAIR silencing reduced methylation of HOXA1, and enhanced the sensitivity of cancer cells to anticancer drugs in SCLC [88]. …”
Section: Long Non-coding Rna In Cancer Cell Drug Resistancementioning
confidence: 99%